2011
DOI: 10.1017/s193029750000262x
|View full text |Cite
|
Sign up to set email alerts
|

Who makes utilitarian judgments? The influences of emotions on utilitarian judgments

Abstract: Recent research has emphasized emotion’s role in non-utilitarian judgments, but has not focused much on characteristics of subjects contributing to those judgments. The present article relates utilitarian judgment to individual disposition to experience various emotions. Study 1 first investigated the relationship among state emotions and utilitarian judgment. Diverse emotions were elicited during judgment: guilt, sadness, disgust, empathy, anger, and anxiety, etc. Using psychological scales, Study 2 found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(11 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Individuals with higher PF1 scores (empathy, altruism, faith in intuition and low callous affect) rated the protagonists' decision against the utilitarian option in both scenarios as more morally appropriate. This result is in line with findings that show negative associations between empathy and utilitarian tendencies [48,101]. Furthermore, there were interaction effects on moral appropriateness ratings between dilemma type and two additional personality factors: PF2 (anxiety, personal distress, low self-esteem) and PF5 (faith in intuition, victim justice sensitivity, obedience to authorities, low NFC).…”
Section: Role Of Personality For Moral Appropriateness Ratingssupporting
confidence: 90%
“…Individuals with higher PF1 scores (empathy, altruism, faith in intuition and low callous affect) rated the protagonists' decision against the utilitarian option in both scenarios as more morally appropriate. This result is in line with findings that show negative associations between empathy and utilitarian tendencies [48,101]. Furthermore, there were interaction effects on moral appropriateness ratings between dilemma type and two additional personality factors: PF2 (anxiety, personal distress, low self-esteem) and PF5 (faith in intuition, victim justice sensitivity, obedience to authorities, low NFC).…”
Section: Role Of Personality For Moral Appropriateness Ratingssupporting
confidence: 90%
“…For example, antisocial personality trait constructs, such as psychopathy, Machiavellianism, and life meaninglessness, are positively related to the endorsement of utilitarian solutions (Bartels & Pizarro, 2011 ). In a study of emotion and moral judgment, Choe and Min ( 2011 ) found that the trait anger was positively correlated with utilitarian judgment, but trait disgust and trait empathy were negatively correlated. A more recent study has demonstrated that the politeness aspects (e.g., respectfulness and etiquette) of agreeableness are positively associated with deontological judgments, whereas the intellectual aspects of openness (e.g., curiosity and cognitive engagement) are positively associated with utilitarian judgments (Smillie et al, 2021 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…First, it extends our knowledge by identifying conditions under which healthcare students’ utilitarian judgments may be related to their positioning as a member of a minority group, a member of a majority group, and in a third-person (neutral) perspective while making judgments in hypothetical moral dilemmas. Second, although personal traits have been proven to be antecedents linked to utilitarian judgment and decision-making (Choe & Min, 2011 ; Djeriouat & Trémolière, 2014 ; Gleichgerrcht & Young, 2013 ), little work has been done to explore the positive and negative aspects of trait-like utilitarian tendencies assessed through the OUS concerning the utilitarian judgments of healthcare students in terms of sacrificial moral dilemmas. Thus, this study may develop our understanding of how one’s utilitarian tendencies account for individual differences in utilitarian judgments.…”
mentioning
confidence: 99%
“…Among them, the ability to state and reason will vary according to the patient’s current conscious state, so it is difficult for patients to get immediate help through objective means. However, some evidence suggests that negative emotions will hinder people’s judgment and DM (Choe & Min, 2011; Raghunathan et al, 2006). Injury and illness often bring a lot of negative emotions to patients, especially in the face of emergencies, patients will have different degrees of fear, anxiety, pain, helplessness, or other negative emotions.…”
Section: The Roles Of Healthcare Design To the Themes Of Ramentioning
confidence: 99%